Applying Participatory Communication Principles in Covid-19 Health Message Dissemination in a Rural South African Municipality - Israel Fadipe; Tshepang Molale (Communicare)
During global pandemics such as COVID-19, authorities around the globe have the responsibility of disseminating preventive health messages as widely as possible to contain the crisis. However, often, as shown by earlier studies (see Molale, 2019; Williams, 2006), governments tend to apply top-down communication approaches and leave local citizens as passive receivers of messages they are required to put into practice. This qualitative inquiry examined how officials of Ratlou Municipality in North-West Province, South Africa, communicated COVID-19 messages to communities in the rural villages of Setlagole and Madibogo. Semi-structured interviews with four municipal officials and focus group interviews with 28 citizens were conducted. The findings suggest that active citizen participation is needed in the communication value chain so that citizens can have a meaningful role in addressing the pandemic. The study is significant in that it shows how linear communication methods are often employed by municipalities to interact with community members are futile, especially when citizens need to be persuaded to adopt new behaviour, such as during health emergencies like cholera, Ebola or COVID-19. Moreover, it adds to the growing corpus of research dedicated to advancing participatory communication as an anchor of citizen participation in South Africa’s local government and beyond.